Tarian Tradisional Didong sebagai Sarana Komunikasi Pendidikan di Komunitas Adat Gayo - T, Zainuddin -; Habibi, Khairul (An-Nuha, 2025)
This study is motivated by the decline in the educational function of the traditional Didong dance within the Gayo indigenous community due to modernization and changing communication patterns among the younger generation. The research aims to analyze the role of Didong as a medium of educational communication and explore strategies for its revitalization to strengthen local-based non-formal education systems. Using a qualitative descriptive approach, data were collected through observations, interviews, and literature reviews involving cultural practitioners, educators, and Gayo youth. The findings reveal that Didong still embodies cultural, religious, and ethical values; however, the younger generation’s understanding and appreciation of its educational messages are diminishing. Revitalization efforts through content innovation and digital integration are effective in engaging youth interest. The study concludes that collaboration among traditional leaders, artists, and educators is crucial to optimize Didong as a tool for character education and the preservation of Gayo cultural identity